A systematic review of consumer satisfaction studies in hospitality journals: conceptual development, research approaches and future prospects. Issue 1 (2nd January 2019) - Prayag, Girish; Hassibi, Saman; Nunkoo, Robin
ABSTRACT: This review paper has the aim of systematically analysing studies published in five hospitality journals over the period 2000 to 2016. The review was organized around four broad themes (conceptual developments, measurement of consumer satisfaction, methods used to research consumer satisfaction, and antecedents and outcomes of consumer satisfaction). The findings show that more than half (110 studies) of studies published across all five journals do not provide a specific definition of consumer satisfaction. Research on this topic is biased toward quantitative methods at the expense of qualitative and mixed methods in all five journals. Researchers have investigated various determinants of customer satisfaction such as equity and fairness perceptions, emotions, corporate social responsibility, and employee satisfaction. The positive consequences of satisfaction on loyalty, behavioural intentions and switching costs are well established. However, several gaps in the current literature are evident and these are highlighted in this review.